NORTH KOREA’S DENUCLEARIZATION TREATY WITH THE UNITED STATES OF AMERICA IN 2018 - Harnanda, Marcellino Abel; Suhanto, Suhanto (Journal of Social Political Sciences, 2023)
This research discusses the denuclearization agreement between The United States and the Republic of Korea, known as the “123 Agreement,” in 2018. This study explains the process of the denuclearization agreement between the two countries and the reasons behind the denuclearization agreement using the de securitization concept, interdependency theory, denuclearization concept, and principal negotiation theory. This research method is qualitative research using library research and official document. The results of this study indicate that peace efforts through denuclearization negotiations experienced ups and downs in the process, and the achievement of the denuclearization negotiation process was based on the respective interests of the United States and North Korea. North Korea has an interests economic sector. North Korea is being hit by poverty and it can be said that the country will go bankrupt. With this agenda, North Korea denuclearizes to secure the economic sector. This research concludes that the denuclearization agreement failed at the second meeting in Hanoi, Vietnam. This failure is because the United States does not want to lift the sanctions imposed in full even though North Korea has stopped testing and closed its nuclear development site